Seroprevalence of Immunoglobulin G Antibodies to Plasmodium falciparum Among Children in Minna, North Central, Nigeria - Hadijah, Usman-Yamman; Samuel, Eke S.; Chidiebere, Otuu A.; Innocent, Omalu C. J.; Abdulkadir, Abubakar (Achievements and Challenges of Medicine and Medical Science Vol. 5, 2024)
Malaria remains a significant global health challenge, predominantly caused by the protozoan parasite Plasmodium falciparum. It is responsible for millions of deaths annually, with children being the most affected group. The study was conducted in Minna, the capital of Niger State in North Central Nigeria, with the objective of determining the seroprevalence of Immunoglobulin G (IgG) antibodies to P. falciparum in children. This cross-sectional study involved 93 children aged 6 months to 17 years, recruited from outpatient departments of selected healthcare facilities in Minna. Blood samples were collected for malaria parasite detection and Enzyme-Linked Immunosorbent Assay (ELISA) testing. The results show a high seroprevalence of IgG antibodies against P. falciparum antigens among children in Minna, indicating widespread exposure to malaria rather than protective immunity. Additionally, the presence of IgG antibodies in microscopically negative samples further indicates the potential for submicroscopic infections, which were confirmed by PCR. Parasite density did not significantly affect IgG responses, with seroprevalence reflecting exposure intensity rather than infection severity. Furthermore, there were no significant differences (P>0.05) in antibody responses across different age groups, suggesting that age does not play a significant role in the development of anti-malarial IgG responses. However, a significant difference (P<0.05) in seroprevalence was observed between males and females, indicating unequal exposure to P. falciparum between the sexes. This chapter provides a comprehensive analysis of the role of IgG antibodies in malaria immunity, highlighting the complex relationship between exposure, antibody production, and protection in children from malaria-endemic regions. The study emphasizes the importance of improving diagnostic tools and the need for further research into the immune responses that could lead to better control and prevention measures.